AB0504 Pregnancy outcome and its relevant factors in patients with systemic lupus erythematosus and rheumatoid arthritis. (15th June 2017) - Takei, H; Kaneko, Y; Takeuchi, T
Abstract : Background: Pregnancy outcome is one of the major concerns to manage systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) since they often affect women in reproductive ages. However, the predictive factors of poor pregnancy outcome and disease flare during pregnancy have not fully investigated. Objectives: To elucidate the factors affecting the pregnancy outcome in patients with systemic erythematosus (SLE) and rheumatoid arthritis (RA). Methods: Patients with SLE and RA in our university between 2012 and 2016 who experienced pregnancy were retrospectively reviewed. Medical information was collected from their chart. Results: Thirty six pregnancies in 26 SLE patients and 26 pregnancies in 21 RA patients were identified. Among SLE pregnancies, the mean age, disease duration and prednisolone dose were 32.7±4.6, 8.9±7.7 years and 5.6±4.1 mg/day, respectively. The disease activity was well controlled (the mean SLEDAI, 2.4±2.1). Live birth pregnancies were 31 (86.1%) and fetal loss occurred in 5 pregnancies (3 spontaneous abortions, 1 ectopic gestation and 1 hydatidiform mole). The mean dose of prednisolone was significantly lower in the pregnancies with live birth than those with fetal loss (4.9±3.4 vs 11.3±3.3mg/day, p=0.02), while proteinuria, SLEDAI, history of lupus nephritis, positivity of antiphospholipid antibodies and anti-SSA/Ro antibodies were not significantly different between the two groups. Maternal lupus flare occurred in 6 (16.7%) during pregnancy or after the delivery and was significantly associated with proteinuria at the time of conception (p=0.02). Low body birth occurred in 9 (29.0%) and was also significantly associated with proteinuria at the time of conception (p=0.002). Among RA patients, the mean age and disease duration were 33.5±5.6 and 9.9±7.4 years. The mean DAS28-ESR, CDAI and HAQ were 2.18±0.88, 3.07±4.10 and 0.30±0.50, respectively and 14 achieved DAS28-ESR remission (<2.6). Seven (26.9%) discontinued biological agents before conception while 8 (34.6%) continued to use biological agents. Although 5 (19.2%) experienced the disease flare during pregnancy, all 26 pregnancies were live birth. The patients who discontinued biological agents more frequently experienced the disease flare than those who continued, during pregnancy or postpartum within 1 year after delivery (85.7% vs 25%, p=0.04). Conclusions: High live birth rates were observed in both SLE and RA pregnancies on the condition of well-controlled disease activity. In SLE pregnancies, less prednisolone dose at the time of conception may be associated with live birth. SLE pregnancies with proteinuria and RA pregnancies with discontinuation of biological agents are associated with disease flare and should be cautiously monitored. References: Arthritis Rheum. 2005;52(2):514–21. Rheumatology (Oxford). 2002;41(6):643–50. J Rheumatol. 2015;42(8):1376–82. Disclosure of Interest: H. Takei: None declared, Y. Kaneko Consultant for: AbbVie, Astellas Pharma, Chugai Pharmaceutical, Bristol-Myers K.K., Eisai, Mitsubishi Tanabe Pharma, Pfizer Japan, and Takeda Pharmaceutical, Speakers bureau: AbbVie, Astellas Pharma, Chugai Pharmaceutical, Bristol-Myers K.K., Eisai, Mitsubishi Tanabe Pharma, Pfizer Japan, and Takeda Pharmaceutical, T. Takeuchi Grant/research support from: Pfizer Japan, Mitsubishi Tanabe Pharma, Eisai, Astellas Pharma, UCB, Chugai Pharmaceutical, Bristol-Myers K.K., Daiichi Sankyo, AbbVie, Janssen Pharmaceutical K.K., Pfizer Japan, Asahi Kasei Pharma, Takeda Pharmaceutical, AstraZeneca K.K., Eli Lilly Japan K.K., and Novartis Pharma K.K., Consultant for: Pfizer Japan, Mitsubishi Tanabe Pharma, Eisai, Astellas Pharma, UCB, Chugai Pharmaceutical, Bristol-Myers K.K., Daiichi Sankyo, AbbVie, Janssen Pharmaceutical K.K., Pfizer Japan, Asahi Kasei Pharma, Takeda Pharmaceutical, AstraZeneca K.K., Eli Lilly Japan K.K., and Novartis Pharma K.K., Speakers bureau: Pfizer Japan, Mitsubishi Tanabe Pharma, Eisai, Astellas Pharma, UCB, Chugai Pharmaceutical, Bristol-Myers K.K., Daiichi Sankyo, AbbVie, Janssen Pharmaceutical K.K., Pfizer Japan, Asahi Kasei Pharma, Takeda Pharmaceutical, AstraZeneca K.K., Eli Lilly Japan K.K., and Novartis Pharma K.K.